Regional Economic Outlook, May 2011, Europe : Strengthening the Recovery. (Regional Economic Outlook, 2011)
The May 2011 Regional Economic Outlook: Europe anticipates that recovery in the region will solidify, with recoveries in advanced and emerging Europe likely to be mutually reinforcing. Advanced Europe continues to absorb most of emerging Europe's exports, while the role of emerging Europe as a market for advanced Europe will expand. Chapters discuss the outlook and policy priorities for advanced and emerging Europe, and analyze the role of financial integration in the buildup and resolution of imbalances within the euro area.